Blood-derived exosomes with anti-inflammatory properties as a new minimally invasive intratesticular therapy for aflatoxin B1-associated chronic testopathy - Fatemeh Mansouri Torghabeh; Mona Keivan; Mandana Fakoor; Reza Dadfar; Mahsa Nazarzadeh; Amir Abdolmaleki (Russian Open Medical Journal)
Rationale — Aflatoxin B1 (AB1) is a dangerous toxin causing severe poisoning and even death in human. Testopathy or even infertility is one of the adverse effects of AB1. Exosomes (Ex) with anti-inflammatory action are known as biological substances derived from body fluids. This experimental study aimed to investigate the possible therapeutic effects of blood-derived Ex on orchitis caused by chronic exposure to AB1. Methods — Male rats (n=18) were distributed among three groups: control, AB1 and AB1+Ex. Orchitis was induced with AB1 (45 μL/kg of rat weight) for 40 days (3 times a week). A day later, 10 IU Ex were injected intratesticularly. A week later, testicular tissue and blood serum were sampled. To confirm the therapeutic effects of Ex, inflammatory genes (TNF-α, IL-6 and IL-10), nitric oxide (NO), malondialdehyde (MDA), testosterone (Tes) and sperm quality were fully evaluated. In addition, H&E staining was used to investigate tissue changes, and immunohistochemical (IHC) assessment was employed to detect the inflammatory protein, galectin-3. The results were analyzed using SPSS (v.19). Results and Discussion — Our results confirmed that Ex therapy can significantly (p<0.05) increase normal morphology (25.01±2.23 in the AB1+Ex group vs. 10.1±0.9 in the AB1 group), number (76.12±6.7 in the AB1+Ex group vs. 27.8±3.2 in AB1 group), and vitality (53.4±6.12 in AB1+Ex vs. 41.9±4.6 in AB1) of sperm cells. Blood-derived Ex significantly (p<0.05) reduced the expression of inflammatory genes (6-fold change was observed in AB1+Ex vs. 17-fold in AB1 for TNF-α, 3-fold change was detected in AB1+Ex vs. 6-fold in AB1 for IL-6, and 2-fold change took place in AB1+Ex vs. 6-fold in AB1 for IL-10), NO (23.1±2.6 in AB1+Ex vs. 62.8±8 0.1 in AB1) and MDA (33.2±4.9 in AB1+Ex vs. 68.9±5.46 in AB1), and increased Tes level (7.1±0.5 in AB1+Ex vs. 1.14±0.3 in AB1) in AB1-affected rats. Histopathological evaluations revealed tissue regeneration after Ex injection. Also, the produced sperm cells were of high quality. Conclusion — Intratesticular injection of Ex from the blood can be considered as a novel anti-inflammatory therapy after AB1-induced orchitis.